Potensi Citicoline dalam Menghambat Penurunan Fungsi Kognitif pada Gangguan Kognitif Ringan: Laporan Kasus Berbasis Bukti - Wiyarta, Elvan; Kristiawan, Febrilian; Sinaga, Gideon Hot Partogi (PT Kalbe Farma Tbk., 2024)
Background: Citicoline has been associated with the improvement of various neurological conditions. This article aims to explore the potential of citicoline in preventing cognitive decline in mild cognitive impairment (MCI). Methods: A comprehensive literature search was conducted through 10 databases. Studies selected should include adult with cognitive impairment using citicoline. Articles were selected according to specified inclusion and exclusion criteria. A critical review and Level of Evidence assessment is done. Results: From a total of 265 studies obtained, 15 were selected and analyzed. The results show that citicoline has the potential to prevent cognitive decline, in patients with MCI, Alzheimer’s disease, Parkinson’s disease, ischemic stroke, and also in healthy individuals. Although results were varied, citicoline has consistently shown significant improvements in Mini-Mental State Examination (MMSE) scores and other cognitive tests. Conclusion: Citicoline has a potential in preventing cognitive decline in MCI. More research is needed to understand its long-term effects and mechanism of action.